Komplementarność działań rodziny i społeczeństwa w wychowaniu - Urbaniak, Andrzej (Wydział Teologiczny, UAM, 2012)
Wychowanie nie jest prostą sumą działań rodziny i instytucji społecznych. Zarówno szkoła, jak i różne organizacje społeczne (w szczególności młodzieżowe) oraz instytucje kościelne podejmujące działania wychowawcze zobowiązane są do respektowania zapisów Karty Praw Rodziny uznającej rodzinę za pierwszą i w pewnym sensie nadrzędną wspólnotę wychowującą. Właściwe efekty wychowawcze można uzyskać tylko w sytuacji spełnienia określonych reguł współpracy wszystkich podmiotów wychowujących. Warto się pochylić nad tymi regułami i poszukiwać nowych sposobów realizacji ich treści.

Upbringing is not merely a mix of activities on the part of the family and social institutions. Schools as well as different social organisations (especially youth ones) or church institutions responsible for upbringing activities are obliged to respect the Charter of the Rights of the Family. According to his document the family is the first and prior community of upbringing. Proper effects can be obtained only when certain conditions and rules of cooperation concerning all the entities engaged in the process of upbringing are implemented. It is worthwhile to discuss these rules and seek new ways of putting them into action.
Complementary Actions of the Family and Community towards Upbringing
Keywords: wychowanie; upbringing; zasada pomocniczości; principle of subsidiarity; komplementarność; complementarity; ekonomia wychowania; economy of upbringing